1993
DOI: 10.1080/03014469300002492
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric-hormonal correlation patterns in fertile and post-menopausal women from Austria

Abstract: Correlations between sex-hormone levels and body dimensions were investigated in a group of women from Vienna. Since sex-hormone concentrations in women are subject to dramatic changes with increasing age, both 124 fertile and 142 postmenopausal women were examined. Twenty-nine anthropometric traits were correlated with oestradiol, the gonadotrophins luteinizing hormone (LH) and follicle-stimulating hormone (FSH), the gestagens progesterone, 17-hydroxyprogesterone and prolactin, and the androgens testosterone,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…It is unlikely that this finding is related to a lack of statistical power, because large sample sizes were studied (19,36). It has been reported that the waist circumference was higher in postmenopausal than in premenopausal women, reflecting the age-related increase in central fatness (39). However, when the confounding effects of age were statistically controlled, no independent effect of menopause was noted on waist circumference tIn this study, women over 50 years of age were assumed to be postmenopausal.…”
Section: Body Fat Distributionmentioning
confidence: 99%
“…It is unlikely that this finding is related to a lack of statistical power, because large sample sizes were studied (19,36). It has been reported that the waist circumference was higher in postmenopausal than in premenopausal women, reflecting the age-related increase in central fatness (39). However, when the confounding effects of age were statistically controlled, no independent effect of menopause was noted on waist circumference tIn this study, women over 50 years of age were assumed to be postmenopausal.…”
Section: Body Fat Distributionmentioning
confidence: 99%
“…Toxoplasma infection was also shown to be associated with higher testosterone levels in males and lower testosterone levels in females . Most studies report a positive correlation between testosterone and estradiol concentrations (Kirchengast, 1993;Handa et al, 1997;Ankarberg and Norjavaara, 1999;Troisi et al, 2003). Thus, the females with low testosterone are expected also to have low levels of estradiol.…”
Section: Discussionmentioning
confidence: 99%
“…The visceral type of obesity is associated with impaired insulin [4] and androgens [5] secretion and responsiveness. A relation was found between body dimensions and thyroid [6] and sex hormone levels [7].…”
Section: Introductionmentioning
confidence: 87%